Introduction of 4-Chlorophenyl: A Protecting Group for the Hydroxy Function - Otsuka, Yuji; Yamamoto, Toshihiro; Fukase, Koichi (Synlett, 2018)
4-Chlorophenyl ether was utilized as a new protecting group for the hydroxy function. This group was readily introduced to a sugar hydroxy group by using diaryliodonium triflate. Regioselective introduction of this protecting group at the vicinal cis-diol was achieved by using a copper catalyst and diaryliodonium triflate. This protecting group is stable under the Lewis acidic conditions of glycosylation, but it can be readily removed by the initial conversion into the corresponding 4-methoxyphenyl ether with use of a Pd catalyst, followed by oxidation with ammonium cerium (IV) nitrate [(NH4)2Ce(NO3)6] (CAN).
Keywords: 4-chlorophenyl ether; 4-methoxyphenyl ether; carbohydrate; protecting group; hydroxy function; regioselective arylation